Proposed Marketing Strategy For PT. Harmony Land Group in Facing off Uncertainty Period - Fithor Muhammad (Eduvest - Journal of Universal Studies, 2022)
PT Harmony Land Group is property developer company for landed houses residential that founded by Fithor Muhammad and Ramadani in 2016. As a company that builds from the scratch, Harmony Land grew so fast, only 5 years, in 2021 Harmony Land already has 25 residential projects with 1004 units in five cities, Depok, Jakarta, Bogor, Sukabumi and Medan. In the fourth year of growth, an unexpected big disaster is coming, Pandemic Covid 19. The property business is greatly affected, people are afraid to leave the house, even less to buy a house. After struggling to survive for two years in a pandemic situation without firing any employees, Harmony Land started looking for the next opportunity to bring Harmony Land to the next level. One big issue that Harmony Land wants to solve is increasing the act per ask at A5 costumer journey. In 2021, the number of ask customers which have already contacted Harmony Land are 17.789, while the number of unit transactions are 105 houses. Only 0,59% act per ask and lost 17.684 potential customers. So, Harmony Land wants to increase the sales by developing a marketing strategy to increase conversion rate act per ask. This research uses the AFI framework. Analysis internal and external that will continue to Formulation strategy and be closed by the Implementation plan of that strategy. Through external analysis, there are many opportunities after pandemic covid where other competitors still wait and see, while customers start to bounce again. From the customer analysis, customers buy houses in Harmony Land because of price, location, design concept and selling service. So, for increasing act per ask, the proposed marketing strategy is to develop thematic residential in many locations with caregiver service to help more customers with many product option each target market area.